If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(2x + 4) = -70 Reorder the terms: -7(4 + 2x) = -70 (4 * -7 + 2x * -7) = -70 (-28 + -14x) = -70 Solving -28 + -14x = -70 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + -14x = -70 + 28 Combine like terms: -28 + 28 = 0 0 + -14x = -70 + 28 -14x = -70 + 28 Combine like terms: -70 + 28 = -42 -14x = -42 Divide each side by '-14'. x = 3 Simplifying x = 3
| [8x+5]=21 | | 72-10x=12 | | -6x+2=3x-79 | | [4x-8]=20 | | x+4=-20-x | | 6x-3=-7x-133 | | 4-3x+2x=-18+2 | | 6=16-13d | | -140=4x-6(-x+10) | | 5y=-2x-15 | | 10x^2-42x+44=0 | | 5x+13=35+7x | | -1-2x-6x=-65 | | 5x-4=30x+16 | | 6x-4(2-x)=14 | | -17=-2x-2x-5 | | 2=8x-32 | | 4(5x-4)+4=-10 | | -4=3x+7(-x-4) | | 15x+10=8x+38 | | -2x-8=-5x+28 | | 9(2n-1)=(8n+4)+3 | | 2(x-1)=24 | | 93=-6x+3(-2x-13) | | 8x-12+7=-3 | | 3x^2+30x-4=0 | | 4x+11=10x-7 | | z+5=-5 | | 4(3x-5)+x=z | | 11y-12=6y+8 | | 6y+4=2y+20 | | 5xa+7=c+a |